Cerebrovascular disorders in patients with type 2 diabetes mellitus and resistant hypertension - A. Yu. Falkovskaya; V. F. Mordovin; A. E. Sukhareva; I. V. Zyubanova; M. A. Manukyan; V. A. Lichikaki; E. I. Tsoi; A. M. Gusakova; N. V. Dorozhkina (Сахарный диабет)
BACKGROUND: Diabetes mellitus (DM) and hypertension are risk factors for cerebral stroke, which are exacerbated by the combination of these diseases. Identifying the factors involved in the development of subclinical brain damage could change the therapeutic strategy for protecting the brain.AIM: to study severity of MRI- sings of brain damage and to identify factors associated with their development in patients with type 2 diabetes and RHTN.MATERIALS AND METHODS: 46 patients with type 2 DM and RHTN were included in a single-center observational uncontrolled study. Patients underwent brain MRI (1.5 Tesla) with calculation of Evans’s index (EI), clinical and lab examinations (HbA1c, glucose, insulin, C-peptide, leptin, resistin, TNF- α, hsCRP, blood aldosterone, insulin-like growth factor-1 (IGF-1)), measurement of the office and ambulatory blood pressure (BP), assessment of peripheral and cerebral vasoreactivity (test with hyperventilation and breath holding).RESULTS: The most frequent MR brain changes were white matter lesions (WML) in periventricular region (PVR) (89%), focal WML (52%) and expansion both of the ventricles (45%) and subarachnoid spaces (65%). Multiple direct correlations were revealed between parameters of carbohydrate metabolism with the degree of WML in PVR and the density of the MR-signal in the basal nucleus (BN), as well as with EI. Adipokines had a direct relationship with the size of the chiasmatic cistern and IE (for resistin), as well as with the density of the MR signal from the BN and IE (for leptin), that was also directly related to the IGF-1 level. The aldosterone level positively correlated with the size of III ventricle. An increase in TNF-α and hsCRP was accompanied by an increase in the density of the MR-signal in the PVR. Impairment of cerebrovascular reactivity is associated with an increase in the density of the MR-signal in PVR and with indirect signs of cerebral atrophy (increase in EI, the size of cisterns and lateral ventricles). Impairment of peripheral vasoreactivity had direct relationship with EI and the expansion of the III ventricle. There were no direct correlations between the severity of MR-sings of brain damage and BP levels.CONCLUSION: The combination of type 2 DM with RHTN is characterized by a high frequency of WML and liquorodynamics disturbances, which related with metabolic, neurohormonal and hemodynamic factors in the absence of a direct relationship with the degree of BP increase